ANALISIS PUTUSAN NOMOR 9/PID.SUS-ANAK/2023/PN.JKT.BRT TENTANG DAKWAAN PIDANA PERSETUBUHAN OLEH ANAK TERHADAP ANAK: Analysis Of Decision Number 9/Pid.Sus-Anak/2023/Pn.Jkt.Brt Regarding The Criminal Charge Of Sexual Intercourse By A Child Against A Child - Citra Kirani; Citra Kirana; Dwi Alfianto (Faculty of Law, Universitas Trisakti, 2024)
Sexual intercourse with children is an act that occurs quite often in Indonesia today. This incident continues to increase over time, so it needs special attention from a legal perspective in Indonesia. The problem formulation of charges existence against the crime of sexual intercourse with children must be handled carefully and thoroughly by implementing applicable laws in order to get a fair decision. So the purpose of this study is to analyze the decision number 9 / pid.sus-anak / 2023 / pn, jkt.brt concerning the criminal charge of sexual intercourse by children against children. This analysis was carried out using the normative legal method with an analytical descriptive approach. The results and conclusions obtained in the decision Number 9 / Pid.SusAnak / 2023 / PN.Jkt.Brt, the Public Prosecutor filed an alternative charge against Children in Conflict with the Law using Article 81 paragraph (2) as the First Charge and Article 82 paragraph (1) Jo. Article 76E as the Second Charge. The appropriate article to be charged with ABH is Article 81 paragraph (1) which clearly describes the rule that everyone is prohibited from committing violence or threats of violence and forcing a child to have sexual intercourse with another person.